2011
DOI: 10.1038/cr.2011.156
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bbtTICAM from amphioxus suggests the emergence of a MyD88-independent pathway in basal chordates

Abstract: The MyD88-independent pathway, one of the two crucial TLR signaling routes, is thought to be a vertebrate innovation. However, a novel Toll/interleukin-1 receptor (TIR) adaptor, designated bbtTICAM, which was identified in the basal chordate amphioxus, links this pathway to invertebrates. The protein architecture of bbtTICAM is similar to that of vertebrate TICAM1 (TIR-containing adaptor molecule-1, also known as TRIF), while phylogenetic analysis based on the TIR domain indicated that bbtTICAM is the oldest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 46 publications
1
32
1
Order By: Relevance
“…6C, 6E). Because the TLR signaling pathway have been well characterized in amphioxus, the bbtIkB protein was also coexpressed with amphioxus MyD88 or TICAM (31,32), and the activation of NF-kB mediated by bbtMyD88 or bbtTICAM was inhibited by bbtIkB in a dose-dependent manner (Fig. 6F).…”
Section: The Journal Of Immunologymentioning
confidence: 99%
See 1 more Smart Citation
“…6C, 6E). Because the TLR signaling pathway have been well characterized in amphioxus, the bbtIkB protein was also coexpressed with amphioxus MyD88 or TICAM (31,32), and the activation of NF-kB mediated by bbtMyD88 or bbtTICAM was inhibited by bbtIkB in a dose-dependent manner (Fig. 6F).…”
Section: The Journal Of Immunologymentioning
confidence: 99%
“…In our previous studies of amphioxus TLRs and related signaling molecules, we provided compelling evidence for a functional intracellular TLR-NF-kB signaling cascade (25,31,32,34). Amphioxus expresses $48 TLRs and .40 TIR-containing adaptors, which suggests an expanded repertoire of adaptors and intermediate signal transducers in its TLR signaling pathways.…”
Section: Oomentioning
confidence: 99%
“…2C-E). Because MyD88-dependent and TICAM-dependent pathways have been demonstrated in amphioxus (18,19), we further used luciferase assays to test whether bbtTIRA, bbtTIRB, and bbtTIRC are involved in amphioxus MyD88-and TICAM-dependent signaling. Results showed that bbtTIRA specifically inhibited the bbtTICAM-dependent activation of NF-kB (Fig.…”
Section: Fluorescence Protease Protectionmentioning
confidence: 99%
“…Amphioxus MyD88 was shown to mediate the activation of NFkB through its middle and death domains, whereas TICAM was shown to mediate the most primitive TRIF-dependent activation of NF-kB (18)(19)(20). Amphioxus SARM plays inhibitory roles in both MyD88-and TICAM-dependent pathways by interacting with MyD88, TRAF6, and TICAM (19,21). Recently, ubiquitination was shown to be essential in regulating the activation of amphioxus NF-kB (22,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation